Features of translating sectoral documentation - Chusovlianova S. V., Baranova A. A. (Human and society, 2017)
the topicality of the research is caused by the need of technical texts translation, as well as with the need of studying the adequacy and equivalency of safety records translation. The study is an attempt of reviewing this problem on the example of a specific text.
Keywords: отраслевая документация; отчет о безопасности; особенность перевода; достижение адекватности перевода отчета о безопасности; sectoral documentation; safety record; features of translation; adequacy of safety record translation